Parents are rapidly getting older in South Korea - Sohn, Kitae (2017)
© 2017 The British Fertility Society. While scholars and policymakers have investigated the causes and consequences of low fertility, they have neglected a related issue: advanced parental age. This is an important issue because advanced parental age adversely affects babies in the short and long run. South Korea recently topped the list of low-fertility countries, and so this study examined the trends in parental age in this country. We analysed all births between 1997 and 2014, the census for 2000 and 2010, and aggregate marriage data to report the trends in age at first marriage, interval from marriage to first birth, and parental age at first birth and at all births. At every stage, age increased rapidly for both parents. As a result, of babies born to fathers aged 20–54, 20.2% were born to fathers aged 35–54 in 2000 with the proportion increasing to 38.7% in 2010–almost double in a single decade. The corresponding figures for mothers increased from 6.7% to 17.2%–more than double. Potential parents and policymakers can use this information to time births more appropriately, thereby reducing risks to babies and mothers.